Triple negative breast cancer - BCL2 in prognosis and prediction. Review - Bouchalova, Katerina; Kharaishvili, Gvantsa; Bouchal, Jan; Vrbkova, Jana; Megova, Magdalena; Hlobilkova, Alice (Current drug targets, 2014)
BACKGROUND: Breast cancer (BC), the most frequent malignancy in women worldwide, is currently diagnosed in about 1.4 million female patients annually. Approximately 10-20% of BC is represented by triple negative breast cancer (TNBC) which is aggressive, the prognosis is poor and patients cannot benefit from targeted treatment based on hormonal or HER2 receptors. For this reason, search for markers that can predict the efficacy of chemotherapy in TNBC is a priority. METHODS AND RESULTS: This review focuses on BCL2 protein as a prognostic marker in TNBC and its potential as a predictor of sensitivity to chemotherapy. CONCLUSION: BCL2 protein expression is a positive prognostic factor in BC. Better survival of patients with BCL2 positivity (BCL2+) has been explained by the correlation with estrogen receptor positive (ER+) status. BCL2+ is however not simply a surrogate marker for ER+. Moreover, BCL2 protein expression is also a positive prognostic marker in the TNBC subgroup. We and others show, that low BCL2 expression was associated with good outcome of TNBC patients treated with both adjuvant and neoadjuvant anthracycline-based chemotherapy. On the other hand, recent studies have shown that a subset of TNBC patients may benefit from the classical adjuvant CMF (cyclophosphamide, methotrexate, 5-fluorouracil) regimen. Given the heterogeneity of TNBC there is an urgent need to find and validate the sensitivity predictors to these regimens making them usable in clinical practice. BCL2 enrichment has been described in the mesenchymal stem-like (MSL) TNBC subgroup.
Keywords: Antineoplastic Combined Chemotherapy Protocols; ženské pohlaví; Biomarkers, Tumor; Treatment Outcome; protokoly antitumorózní kombinované chemoterapie; triple-negativní karcinom prsu; Humans; Proto-Oncogene Proteins c-bcl-2; lidé; výsledek terapie; Triple Negative Breast Neoplasms; protoonkogenní proteiny c-bcl-2; nádorové biomarkery; Female